Metabonomics analysis of Zi goose follicular granulosa cells using ENO1 gene expression interference. Issue 3 (10th December 2019) - Ji, Hong; Guo, Wenjin; Niu, Chunyang; Li, Yue; Lian, Shuai; Zhan, Xuelong; Guo, Jingru; Zhen, Li; Yang, Huanmin; Li, Shize; Wang, Jianfa
Abstract: The Zi goose is native to North‐east China and is noted for its high egg production. Alpha enolase ( ENO1 ) is a glycolytic enzyme which functions as a plasminogen receptor in follicular granulosa cells (FGCs), with several studies showing that FGCs can support follicular development. By transfecting the ENO1 interfering plasmid (shRNA) into FGCs, ENO1 expression in these cells was downregulated, suggesting the successful knock‐down of ENO1 in these cells. In this knock‐down model, we detected 13 metabolites from FGCs using LC/MS. When compared with the non‐coding shRNA (NC) group, the lower level metabolites were (R)‐(+)‐citronellic acid, altretamine, 3‐hydroxycaproic acid, heptadecanoic acid, cholecalciferol vitamin D3, indole, benzoic acid, capric acid, caffeic acid, azelaic acid, 3, 4‐dihydroxyhydrocinnamic acid and cholic acid, while oleic acid was detected at high levels. To further examine the results of metabolomics, six key metabolites were verified by gas chromatography‐mass spectrometry (GC‐MS). We found that vitamin D3, indole, benzoic acid, capric acid and cholic acid were significantly downregulated in the shRNA group, while oleic acid was significantly upregulated. This observation was consistent with the metabolomics data. Through these studies, we found that decreased ENO1 levels altered certain metabolite levels in FGCs.